Bacteriostatic and Haemolytic Activities of Extracts and Compounds of Commiphora swynnertonii - Zaituni Msengwa*; David Credo; Magesa Mafuru; James Mwesongo; Faith Philemon Mabiki; Beda John Mwang'onde; Madundo Mkumbukwa Mtambo; Lughano Jeremy Kusiluka; Robinson Hammerthon Mdegela; John Elmerdahl Olsen (Iranian Society of Pharmacognosy, 2023)
Background and objective: Commiphoraswynnertonii (Pax) is used in traditional medicine to treat infectious diseases. Previous studies have reported antimicrobial activity of this plant;however, the activity of compounds that are present in extracts of this plant has not been thoroughly documented. Likewise, the primary mode of action (bactericidal or bacteriostatic) and the possible toxicity on red blood cells have not been reported. Methods: Extracts of leaves, whole root, root bark, root wood, whole stem, stem bark and stem wood, were produced using hexane, dichloromethane, methanol and water. Cold and hot extraction methods were employed. Antibacterial activity of extracts was tested against selected medically important Gram-positive and Gram-negative bacteria by growth inhibition, minimum inhibitory concentrations and time kill assays. Moreover, haemolytic activity against sheep red blood cells was determined in vitro. Results: The hexane extracts of whole root and root bark, methanol extracts of root wood, and dichloromethane extracts from the leaves of C. swynnertonii inhibited the growth of S. aureus. MIC values for the extracts and compounds, indicated moderate activity against Gram-positive bacteria (Staphylococcus aureus, Streptococci species and Enterococci species) while the activity against Gram-negative bacteria (Escherichia coli, Klebsiella species, Pseudomonas aeruginosa, Salmonella species, Shigella sonnei and Yersinia enterocolitica) was weak. Time kill profiles showed the extracts have bacteriostatic activity against S. aureus, and low haemolytic effect, except for extracts of whole root and leaves at the concentration of 1000 µg/mL. Conclusion:Extracts of C. swynnertonii showed bacteriostatic activity against Gram-positive bacteria with low toxicity on red blood cells.